The effects of contaminant microorganism towards Chelonia mydas eggs hatchery results in Pangumbahan Green Sea Turtles Conservation, Sukabumi, Indonesia - TOUFAN GIFARI; DEWI ELFIDASARI; IRAWAN SUGORO (Biodiversitas Journal of Biological Diversity, 2018)
Gifari T, Elfidasari D, Sugoro I. 2018. The effects of contaminant microorganism towards Chelonia mydas eggs hatchery results in Pangumbahan Green Sea Turtles Conservation, Sukabumi, Indonesia. Biodiversitas 19: 1207-1212. Green sea turtles (Chelonia mydas) is an endangered species, in which its population is continuously decreasing caused by a number of factors. Microorganisms are suspected to have important role in declining eggs hatching success. The aim of this study was to investigate the role of microbial contaminant on the egg hatching success at the green sea turtles conservation area in Pangumbahan needs. The microbial contaminants detection was carried out on the eggs at the semi-natural hatching nest. RAL with three times repetitions was selected to figure out the correlation between microbial contaminants and hatching success was. The eggs were incubated at three different depths, i.e., 40, 60, and 80 cm. The results showed that the Gram-negative microorganisms were from the coliform bacteria such as E. coli, Salmonella and Shigella. Meanwhile, the fungi were dominated by mildew and yeast. The hatching success rate was 93.34% in 80 cm depth, 85% in 60 cm depth and 60% in 40 cm depth. HSD Tukey test shows the effects of various nesting depths towards the hatchery percentage (p?0.05) with the correlation test of microorganisms contaminant shows negative value meaning the level of contaminant microorganism is an inverse proportion to the hatchery results.